Recent developments, challenges and opportunities in genome editing for crop science from a societal perspective - Venkataraman, Srividhya; Zaruk, David; Hefferon, Kathleen (Frontiers in Genome Editing, 2025)
Genome editing has presented enormous potential in the fields of medicine and agriculture. Here, we explore the social and regulatory aspects of genome editing from the perspective of food security. We provide recent examples of crop genome editing successes. We discuss the current regulatory framework for genome edited crops in North America and Europe, and present how public perception can influence international policies and trade.